Optimizing the Role of BNPT in Preventing Terrorism Financing Using Cryptocurrency in Indonesia - Ariani, Okta; Ibrahim, Aji Lukman (Universitas Semarang, 2024)
The development of cryptocurrency technology is the latest innovation in the financial sector. The purpose of this study is to determine the efforts made by BNPT and to assess the ideal regulations in addressing this issue in the future. Through the use of blockchain technology, users can transact anonymously. This research is considered as a normative juridical research equipped with interviews using a statutory approach. Sources of data obtained from secondary data which includes primary, secondary, and tertiary legal materials. The novelty of the study shows that the BNPT establish the CTF Task Force which aims to combat terrorism financing through cryptocurrency and based on several previous studies and after looking at the above-mentioned examples of the phenomenon of terrorism financing, it is undeniable that many terrorists are trying to utilise cryptocurrencies to fund criminal acts. This has resulted in the issue of a legal or regulatory vacuum regarding the use of cryptocurrencies, in this case, the Commodity Futures Trading Supervisory Agency Regulation No. 6/2019 on Implementation of Anti-Money Laundering and Terrorism Financing Prevention In its future endeavors, there is a need for specific regulations to ensure that the implementation process of the CTF Task Force with other agencies can be carried out more optimally.